PERANCANGAN SISTEM APLIKASI PEMBAYARAN MENGGUNAKAN QR-CODE DI KANTIN UNIVERSITAS DINAMIKA BANGSA - M. Ade. Maulana; mikhail ibrahim; Hendryzal; Dodo Zaenal Abidin (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2023)
Payment systems have become crucial in the present time to enhance efficiency and effectiveness in conducting transactions. The payment process at the canteen of Dinamika Bangsa University, Kota Baru, is currently being carried out conventionally, which is inefficient in terms of time and place. This can lead to delays when sellers have to provide change and can result in long queues. To address these issues, a system is needed to facilitate transactions for both sellers and buyers. The chosen method for developing this system is the waterfall approach, utilizing UML (Unified Modeling Language) tools, including use case diagrams, activity diagrams, and class diagrams. The system is designed using the Dart programming language and an FireBase database. This research culminates in a payment application using QR codes, which will assist the canteen personnel in conducting transactions at Dinamika Bangsa University, Kota Baru.